Syntax of Hungarian Nouns and Noun Phrases, Volume 1 - Alberti, Gábor; Laczkó, Tibor (Amsterdam University Press, 2017)
These books aim to present a synthesis of the currently available syntactic knowledge of the Hungarian language, rooted in theory but providing highly detailed descriptions, and intended to be of use to researchers, as well as advanced students of language and linguistics. As research in language leads to extensive changes in our understanding and representations of grammar, the Comprehensive Grammar Resources series intends to present the most current understanding of grammar and syntax as completely as possible in a way that will both speak to modern linguists and serve as a resource for the non-specialist.